(untitled) (African Journal of Biomedical Research, 2021)
Assessment of bacterial contamination was carried out on ready to eat fruits and vegetable sold in Oja-Oba Market, Ilorin. Nine (9) samples of two (2) different fruits (watermelon and pawpaw) and vegetable (carrot) were collected randomly from different stationery vendors. Samples were analyzed to study the total bacterial count, total coliform count, total Salmonella count and total Staphylococcus count using 10-fold serial dilution and plate count method. Pure colonies were isolated using streak plate method and subjected to biochemical tests using standard procedures. Ten (10) antibiotics were used for susceptibility test against the bacterial isolates using disk diffusion method. Mean microbial load ranged from 60.17 ± 3.10 x 104 - 158.67 ± 6.90 x 104 cfu/ml for vendor A; 61.83 ± 2.60 x 104 - 144.33 ± 4.24 x 104 cfu /ml for vendor B and 56.83 ± 3.53 x 104 – 88.50 ± 3.10 x 104 cfu/ml for vendor C. Total coliform count ranged from 7.80 ± 1.10 x 104 – 26.70 ± 2.82 x 104 cfu/ml, total Staphylococcus count ranged from 5.00 ± 0.24 x 104 – 21.17 ± 3.06 x 104 cfu/ml and total Salmonella count ranged 8.84 ± 1.18 x 104 - 11.67 ± 1.41 x 104 cfu/ml. Antibiotics susceptibility test ranged from10.00 ± 0.00 – 26.50 ± 0.21 mm. Ciprofloxacin and gentamycin had an average diameter of zone of inhibition at 24.50 ± 0.71 and 26.50 ± 0.21 mm respectively. It can be concluded that ready to eat fruits and vegetables sold in Oja-Oba Market contain considerable numbers of pathogenic bacteria